2013
DOI: 10.1128/aem.03277-12
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Porcine β-Defensins 1 and 2 upon Individual and Combined Fusarium Toxin Exposure in a Swine Jejunal Epithelial Cell Line

Abstract: dDefensins are small antimicrobial peptides (AMPs) that play an important role in the innate immune system of mammals. Since the effect of mycotoxin contamination of food and feed on the secretion of intestinal AMPs is poorly understood, the aim of this study was to elucidate the individual and combined effects of four common Fusarium toxins, deoxynivalenol (DON), nivalenol (NIV), zearalenone (ZEA), and fumonisin B1 (FB1), on the mRNA expression, protein secretion, and corresponding antimicrobial effects of po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 58 publications
0
18
0
Order By: Relevance
“…Thus, DON (1 to 20 µM) affects the expression of proteins involved in the epithelial innate immunity, including COX-2 and β-defensins [113,114,115]. Similarly, numerous studies using animal and human cells have demonstrated that DON stimulates the expression and secretion of interleukin-8 (IL-8), a chemoattractant cytokine causing the recruitment/activation of circulating immune cells and thus potentially participating indirectly in the central effects of DON in terms of feed refusal and emesis.…”
Section: Pathophysiological Effects Of Donmentioning
confidence: 99%
“…Thus, DON (1 to 20 µM) affects the expression of proteins involved in the epithelial innate immunity, including COX-2 and β-defensins [113,114,115]. Similarly, numerous studies using animal and human cells have demonstrated that DON stimulates the expression and secretion of interleukin-8 (IL-8), a chemoattractant cytokine causing the recruitment/activation of circulating immune cells and thus potentially participating indirectly in the central effects of DON in terms of feed refusal and emesis.…”
Section: Pathophysiological Effects Of Donmentioning
confidence: 99%
“…New data on in vitro toxicity of NIV published since the last evaluation (EFSA CONTAM Panel, ) confirm previously known effects such as induction of apoptosis, cytotoxicity, increased secretion of anti‐haematopoietic macrophage inflammatory proteins, reduction of mitochondrial activity and reduced cell proliferation (Wan et al., ,b,c; Nagashima and Nakagawa, ; Park et al., ; Cheat et al., ; Del Regno et al., ; Vejdovszky et al., ).…”
Section: Toxicitymentioning
confidence: 54%
“…One urine sample contained only one mycotoxin, while 20 combinations of two or up to seven mycotoxin urinary biomarkers were observed; more than 70% of the urines contained ve or more different mycotoxins. Complex mixture toxicology remains poorly examined though several groups have recently examined combined effects in vitro [47,48,49,50,51,52,53,54,55,56,57,44,45], with animal studies being more limited [58,59]. These studies remain hard to interpret for public health decisions, but some suggest more than additive effects, thus the mixtures reported here and elsewhere highlight signi cant knowledge gaps.…”
Section: Discussionmentioning
confidence: 95%